Purification and Characterization of Peanut Lipoxygenase Enzime - B A.S Santosa; A Eliana; S Widowati (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2005)
Fat oxidation of peanut is a serious problem, because it could reduce of peanut quality and form a hydroperoxide compound. Hydroperoxide could be broken down into acid, ketone and low peptide, and resulted in volatile compounds with undersirable aroma. Extraction on enzyme was carried out by water, while purification and fractination were conducted using ammonium sulphate and chromatography. The objective of this research was to evaluate of the protein fraction, lipoxygenase properties, and enzyme activity during fractionation. The result showed that the highest fraction of protein was globulin, i.e 41-48% of total extracted protein, and the activity of lipoxygenase enzyme in the albumin fraction was 40-54% of the total activity. Purification of lipoxygenase enzyme was conducted by using ammonium sulphate (40-60% saturated) and this increased its specific activity up to 2.0-4.2 timer from the crude enzyme. Separation of lipoxygenase enzyme using sephadex G-150 revealed 3 (tree) peaks of activities, with specific activities 6.0-70.0 fold of the crude enzyme. Lipoxygenase enzyme of gajah variety denatured when heated at 700C during 30 minutes. The activition energy of lipoxygenase enzyme from Gajah variety (19.083 Cal/Mol) was relatively lower than 1509 and 1512 which were, 25.446 Cal/Mol and 24.780 Cal/Mol, respectively. The result showed that lipoxygenase enzyme from Gajah variety was relativeky more heat stable as compared to the 1509 and 1512 lines. Lower activation energy of lipoxygenase enzyme indicated that effect of temperature alteration toward ‘k’ value was smaller. Lipoxygenase enzyme was active at pH higher than 3.0 or lower than 10.0. the data indicated that ‘Km’ value of lipoxygenase enzyme from Gajah variety was higher than that of 1509 and 1512 lines. It means that lipoxygenase enzyme from 1509 and 1512 lines more reactive that gajah variety. Key words : Lipoxygenase, peanut, purification